Problems of formation and effective use of enterprise staff - Babiak, Halyna; Kotys, Nataliya (Регіональні аспекти розвитку продуктивних сил України, 2020)
The article studies the processes of formation and implication of the personnel of the enterprise in terms of labor market development. The recommendations for improving the formation of the personnel as a factor in improving the efficiency of activities are developed.The peculiarities of the personnel formation and implication the LLC «Pearl of Podillya» have been revealed, in particular, the open personnel policy of the LLC indicates the transparency of the enterprise for potential employees of any level. More than 30% of the employees are under 40years  of age and have the appropriate professional knowledge and skills.Disappointing trends in the dynamics of the number of employees of the LLC (the annual decrease in the number of employees, which is reflected in the increase of fluctuation on dismissal (30% in mid –2020), decrease in fluctuation on admission – 35%) are pointed at.The article emphasizes that combination of economic and social perspectives must be taken into account when improving the personnel management system at a limited liability company.It is proposed to take into account the experience of other countries and successful companies in the sphere of personnel development. However, copying foreign methods of work with staff without taking into account the characteristics of Ukrainian enterprises can have a significant negative effects - both economic and psychological, because in the work with people the mentality, traditions, features of the spiritual and socio-economic environment in which individuals grew and formed are of great importance.The recommendations, proposals and measures have been developed to improve the problem of raising the efficiency of the organization in the sphere of formation and implication of the personnel.